2020
DOI: 10.3390/d12020072
|View full text |Cite
|
Sign up to set email alerts
|

Urbanization and Human Population Favor Species Richness of Alien Birds

Abstract: Human activities like urbanization and agriculture affect spatial biodiversity patterns. The presence and activities of humans richly benefit alien species, but native species usually decline in human-impacted areas. Considering that the richness of alien and native species are inter-related, we explored the effect of human population density, human-related land uses (agricultural and urban), and natural land area on avian (alien and native) species richness of Massachusetts for two time periods using Generali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 73 publications
1
4
0
Order By: Relevance
“…The later species is regarded as one of the 100 worst alien species in Europe (Brochier et al, 2010) and may in future expand throughout the Bangkok region threatening native cavity nesting species as is thought to be the case elsewhere in the Rose‐ringed Parakeet's non‐native range (Strubbe & Matthysen, 2009). Finally, and despite the low number of non‐native species, we found that the richness of non‐native species increased along the urbanization intensity gradient, contrasting with declines in species richness for all other groups, therefore providing support for conclusions that urban areas favor non‐native species (Lazarina et al, 2020; Tomasevic & Marzluff, 2017).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The later species is regarded as one of the 100 worst alien species in Europe (Brochier et al, 2010) and may in future expand throughout the Bangkok region threatening native cavity nesting species as is thought to be the case elsewhere in the Rose‐ringed Parakeet's non‐native range (Strubbe & Matthysen, 2009). Finally, and despite the low number of non‐native species, we found that the richness of non‐native species increased along the urbanization intensity gradient, contrasting with declines in species richness for all other groups, therefore providing support for conclusions that urban areas favor non‐native species (Lazarina et al, 2020; Tomasevic & Marzluff, 2017).…”
Section: Discussionsupporting
confidence: 76%
“…Urban assemblages, including avian ones, are often considered to include a high proportion of established non‐native species (Lazarina et al, 2020; Marzluff, 2001). Yet, only a small proportion of species detected in our surveys (five of the 142 recorded species, 3.5%) were non‐native to the Bangkok region and, of these, only two species were widespread (Rock Pigeon Columba livia and Zebra Dove Geopelia striata ).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, alien species feel more comfortable in highly populated areas where the ecosystem functionality is adulterated, and they can exploit many gaps efficiently to find food and nesting resources [8][9][10]. In areas where the ecosystem structure is weaker, they can more easily find a suitable niche.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies of the effects of urbanization on avian wildlife compare populations along an urban to rural gradient, but our ndings contribute to a growing body of evidence that suggest that rural land use changes may affect species alongside urbanization (e.g. Kumar and Kaur Kler 2021, Lazarina et al 2020).…”
Section: Human Impacts Beyond Urbanizationmentioning
confidence: 75%